2006
DOI: 10.1111/j.1075-122x.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging Estrogen Receptor-Negative/ Progesterone Receptor-Negative/HER-2-Negative Patient: A Promising Candidate for Epidermal Growth Factor Receptor-Targeted Therapy?

Abstract: While epidermal growth factor receptor (EGFR)-targeted therapy has been very promising in a number of human malignancies, to date these targeted biologic agents have not proven effective in breast cancer. However, the EGFR tyrosinase inhibitors have been used indiscriminately against all types of breast tumors, perhaps missing a subpopulation of patients who may be prime candidates for EGFR-targeted therapy. In this communication we propose that patients with estrogen receptor (ER)-negative/progesterone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Increased HER1 protein expression is described in about 40% of BC, (ranging from 14% to 91% of all primary BC). High expression is described in triple negative breast cancer and metaplastic cancer (mostly basal-like) 7,14,[64][65][66][67][68][69][70][71][72] . HER1 overexpression was found in 30% of inflammatory breast cancer (IBC).…”
Section: The Her Familymentioning
confidence: 99%
“…Increased HER1 protein expression is described in about 40% of BC, (ranging from 14% to 91% of all primary BC). High expression is described in triple negative breast cancer and metaplastic cancer (mostly basal-like) 7,14,[64][65][66][67][68][69][70][71][72] . HER1 overexpression was found in 30% of inflammatory breast cancer (IBC).…”
Section: The Her Familymentioning
confidence: 99%
“…In a recently reported analysis of participants in the Carolina Breast Cancer study 64% of Caucasian patients had a luminal A breast cancer subtype compared with only 48% of African-American patients, 11% of Caucasian patients had a luminal B breast cancer subtype compared with 8% of African-American patients, 5% of Caucasian patients had a HER2 overexpressing breast cancer subtype compared with 7% of African-American patients, and only 11% of Caucasian patients had a basal breast cancer subtype compared with a 22% of African-American patients [24]. We reported previously that 64% of ER negative/PR negative/HER2 negative breast tumors express epidermal growth factor receptor (EGFR) and that 67% of this group belongs to the basal subtype of breast carcinomas [15,20]. EGFR is a member of the human epidermal growth factor family of transmembrane tyrosine kinases that activate a number of signaling pathways involved in cell proliferation and carcinogenesis [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…We reported previously that 64% of ER negative/PR negative/HER2 negative breast tumors express epidermal growth factor receptor (EGFR) and that 67% of this group belongs to the basal subtype of breast carcinomas [15,20]. EGFR is a member of the human epidermal growth factor family of transmembrane tyrosine kinases that activate a number of signaling pathways involved in cell proliferation and carcinogenesis [15][16][17][18][19]. Despite initial absence of promising results with the use of EGFR-targeted therapies in breast cancer, a growing number of studies suggested interactions of EGFR-mediated signaling and endocrine pathways [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple-negative breast cancer (TNBC), which represents approximately 15% of all breast cancers (3) and shows high recurrence and poor survival rates (4), is defined by the lack of estrogen receptor (ER), progesterone receptor (PR) and epidermal growth factor receptor 2 (HER2/cerbB2/ EGFR2) expression (5). Thus, to date, TNBC lacks effective targeted therapies.…”
Section: Introductionmentioning
confidence: 99%